Trellis systems ameliorate heat damage by regulating canopy temperature, photosynthetic efficiency and leaf microstructure of grapevine - Luo, Ling; Liu, Xinya; Lyu, Xiulan; Zhong, Qi; Ma, Yijun; Li, Ran; Liu, Wei (Frontiers in Plant Science, 2026)
IntroductionGlobal warming has made heat stress a major constraint on grapevine growth and grape production. This study aimed to evaluate the heat tolerance of three prevalent trellis systems—V-shaped (VT), upward-trained pendulous (U-PT), and H-shaped (HT)—for Vitis labruscana × V. vinifera ‘Shine Muscat’. We specifically tested the hypothesis that U-PT enhances heat tolerance by optimizing canopy structure to mitigate high-temperature stress, thereby alleviating its negative impacts on stomatal function, chloroplast integrity, and photosynthetic performance.MethodsUnder summer rain-shelter cultivation, the three trellis systems were compared using five-year-old ‘Shine Muscat’ grapevines based on canopy temperature, relative humidity, leaf sunburn, chlorophyll content, stomatal morphology, chloroplast ultrastructure, leaf gas exchange, and chlorophyll fluorescence.ResultsUnder prolonged heat stress, stomatal aperture dimensions and aperture ratio decreased (p < 0.05) without significant changes in stomatal density (p > 0.05). Chloroplasts displayed volumetric expansion and substantial lipid droplet accumulation, with particularly pronounced chloroplast envelope disintegration in HT. From Day 3 to Day 15 of prolonged high-temperature stress, net photosynthetic rate (Pn), stomatal conductance (gs), transpiration rate (Tr), intercellular CO₂ concentration (Ci), chlorophyll content, and photochemical quenching coefficient (qP) initially increased, peaking on Day 3 or Day 6, then progressively declined. Maximum energy conversion efficiency (Fv/Fm), actual photochemical efficiency (ΦPSII) and non-photochemical quenching coefficient (NPQ) remained stable on Day 3. Subsequently, Fv/Fm and ΦPSII gradually decreased, while NPQ gradually increased. Comparative analysis revealed U-PT maintained the lowest intensity and shortest duration of high canopy temperatures along with higher canopy relative humidity, exhibited the minimal leaf sunburn damage index, and sustained the highest stomatal aperture, Pn, Fv/Fm, ΦPSII, qP, and chlorophyll content, and most stable chloroplast structure, whereas HT performed poorest. The principal component analysis (PCA) confirmed U-PT as the most heat-tolerant trellis system.DiscussionThese findings could provide insights into the responses and adaptions of grapevines to heat stress and aid in the optimization of heat-tolerant trellis systems under everchanging climatic conditions.